Website Sebagai Media Publikasi Kegiatan Perayaan Hari Jadi Kota Pekanbaru Tahun 2022 - Wahyuliarni, Aldha; Syahputra, Aldino; Irvansyah, Muhammad; Haristo Pratama, Muhammad; Mariska, Revi; Hartono, Toni (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2023)
This research discusses the media publication of the 238th Pekanbaru City Anniversary in 2022 through the website www.pekanbaru.go.id. The 238th Anniversary of the City of Pekanbaru in 2022 will be filled with a series of activities published through the official Pekanbaru City government website and managed by the Communication and Information Office for Communication and Public Information Management. This research aims to determine the website as a publication medium for Pekanbaru City Anniversary celebrations. The method used in this research is qualitative. The results of this research show that the website is used as a publication medium for Pekanbaru City Anniversary celebrations in providing various kinds of information about activities, competitions and other interesting events. Information is packaged via the website in the form of press releases, photos and videos. In this context, the use of the website as a publication medium for the Pekanbaru City Anniversary celebration provides easy access to information for the public, especially regarding the 238th Pekanbaru City Anniversary celebration in 2022 regarding the activities being held.